Adaptive responses of plants to light stress: mechanisms of photoprotection and acclimation. A review - Khan, Imran; Sohail,; Zaman, Shah; Li, Guihua; Fu, Mei (Frontiers in Plant Science, 2025)
Plants depend on solar energy for growth via oxygenic photosynthesis. However, when light levels exceed the optimal range for photosynthesis, it causes abiotic stress and harms plant physiology. In response to excessive light, plants activate a series of signaling pathways starting from the chloroplast and affecting the entire plant, leading to stress-specific physiological changes. These signals prompt various physiological and biochemical adjustments aimed at counteracting the negative impacts of high light intensity, including photodamage and photoinhibition. Mechanisms to protect against light stress involve scavenging of chloroplastic reactive oxygen species (ROS), adjustments in chloroplast and stomatal positioning, and increased anthocyanin production to safeguard the photosynthetic machinery. Given that this machinery is a primary target for stress-induced damage, plants have evolved acclimation strategies like dissipating thermal energy via non-photochemical quenching (NPQ), repairing Photosystem II (PSII), and regulating the transcription of photosynthetic proteins. Fluctuating light presents a less severe but consistent stress, which has not been extensively studied. Nevertheless, current research indicates that state transitions and cyclic electron flow play crucial roles in helping plants adapt to varying light conditions. This review encapsulates the latest understanding of plant physiological and biochemical responses to both high light and low light stress.